Contrasted Chemical Weathering Rates in Cratonic Basins: The Ogooué and Mbei Rivers, Western Central Africa - Moquet, Jean-Sébastien; Bouchez, Julien; Braun, Jean-Jacques; Bogning, Sakaros; Mbonda, Auguste Paulin; Carretier, Sébastien; Regard, Vincent; Bricquet, Jean-Pierre; Paiz, Marie-Claire; Mambela, Emmanuel; Gaillardet, Jérôme (Frontiers in Water, 2021)
Despite the absence of tectonic activity, cratonic environments are characterized by strongly variable, and in places significant, rock weathering rates. This is shown here through an exploration of the weathering rates in two inter-tropical river basins from the Atlantic Central Africa: the Ogooué and Mbei River basins, Gabon. We analyzed the elemental and strontium isotope composition of 24 water samples collected throughout these basins. Based on the determination of the major element sources we estimate that the Ogooué and Mbei rivers total dissolved solids (TDS) mainly derive from silicate chemical weathering. The chemical composition of the dissolved load and the area-normalized solute fluxes at the outlet of the Ogooué are similar to those of other West African rivers (e.g., Niger, Nyong or Congo). However, chemical weathering rates (TZ+sil rate expressed as the release rate of the sum of cations by silicate chemical weathering) span the entire range of chemical weathering intensities hitherto recorded in worldwide cratonic environments. In the Ogooué-Mbei systems, three regions can be distinguished: (i) the Eastern sub-basins draining the Batéké Plateaux underlain by quartz-rich sandstones exhibit the lowest TZ+sil rates, (ii) the Northern sub-basins and the Mbei sub-basins, which drain the southern edge of the tectonically quiescent South Cameroon Plateau, show intermediate TZ+sil rates and (iii) the Southern sub-basins characterized by steeper slopes record the highest TZ+sil rates. In region (ii), higher DOC concentrations are associated with enrichment of elements expected to form insoluble hydrolysates in natural waters (e.g., Fe, Al, Th, REEs) suggesting enhanced transport of these elements in the colloidal phase. In region (iii), we suggest that a combination of mantle-induced dynamic uplift and lithospheric destabilization affecting the rim of the Congo Cuvette induces slow base level lowering thereby enhancing soil erosion, exhumation of fresh primary minerals, and thus weathering rates. The study points out that erosion of lateritic covers in cratonic areas can significantly enhance chemical weathering rates by bringing fresh minerals in contact with meteoric water. The heterogeneity of weathering rates amongst cratonic regions thus need to be considered for reconstructing the global, long-term carbon cycle and its control on Earth climate.